Kinetics of Heterogeneous Background in Stargardt’s Disease over Time - Eduardo Rodríguez-Bocanegra; Marc Biarnés; Míriam Garcia; Lucía Lee Ferraro; Manuel Dominik Fischer; Jordi Monés (Life, 2022)
Stargardt’s disease (STGD1) is caused by mutations in the ABCA4 gene. Different lesions characterised by decreased autofluorescence levels are found in fundus autofluorescence (FAF) from STGD1 patients and could be used as outcome indicators for disease progression. We investigated the fate of foci with reduced autofluorescence (FRA) within the heterogeneous background of STGD1 patients using FAF imaging. Genetically confirmed STGD1 patients presenting heterogeneous background autofluorescence on high-quality FAF images at a minimum of two visits at least 12 months apart were chosen. A grid centred on the fovea was used to define five different zones. Within each zone, five FRA were randomly selected for each eye. The eccentricity of foci was determined at different time points for each patient. Analysis of 175 randomly chosen FRA showed consistent centrifugal displacement over time, most notably in eyes showing areas with definitely decreased autofluorescence. Interestingly, FRA did not leave an area of hypo-autofluorescence on FAF in locations where they were previously located. These findings may help to better understand STGD1 progression, improve FAF interpretation, and shed light on the nature of heterogeneous background.